Associative role of HLA-DRB1 as a protective factor for susceptibility and progression of Parkinson’s disease: a Chinese cross-sectional and longitudinal study - He, Raoli; Zeng, Yuqi; Wang, Chaodong; Chen, Lina; Cai, Guoen; Chen, Ying; Wang, Yingqing; Ye, Qinyong; Chen, Xiaochun (Frontiers in Aging Neuroscience, 2024)
Background: Previous genome-wide association studies investigating the relationship between the HLA-DRB1 and the risk of Parkinson's disease (PD) have shown limited racial diversity and have not explored clinical heterogeneity extensively.The study consisted of three parts: a case-control study, a cross-sectional study, and a longitudinal cohort study. The case-control study included 477 PD patients and 477 healthy controls to explore the relationship between rs660895 and PD susceptibility. The cross-sectional study utilized baseline data from 429 PD patients to examine the correlation between rs660895 and PD features. The longitudinal study included 388 PD patients who completed a 3-year follow-up to investigate the effects of rs660895 on PD progression.In the case-control study, HLA-DRB1 rs660895-G allele was associated with a decreased risk of PD in allele model (adjusted OR=0.72, p=0.003) and dominant model (AG+GG vs. AA: adjusted OR= 0.67, p = 0.003). In the cross-sectional analysis, there was no association between rs660895 and the onset age, motor phenotype, or initial motor symptoms. In the longitudinal analysis, PD patients with the G allele exhibited a slower progression of motor symptoms (MDS-UPDRS-III total score: β = -5.42, p < 0.001, interaction p time × genotype < 0.001) and non-motor symptoms (NMSS score: β = -4.78, p = 0.030, interaction p time × genotype < 0.001).Our findings support HLA-DRB1 rs660895-G allele is a protective genetic factor for PD risk in Chinese population. Furthermore, we also provide new evidence for the protective effect of rs660895-G allele in PD progression.